Investigation on the Usefulness of Sulfamethoxazole Trimethoprim Combination Small Tablets in Pediatric Pharmacotherapy: A Single Center Observational Study Using a Questionnaire - Jumpei Saito; Miho Yamaguchi; Seiichi Shimizu; Kyoko Chiba; Tomoyuki Utano; Akinari Fukuda; Seisuke Sakamoto; Mureo Kasahara; Akimasa Yamatani (MDPI AG, 2022)
Sulfamethoxazole trimethoprim (ST) combinations are used to prevent infection in immunocompromised patients. In pediatric patients, conventional ST combination tablets (cTab) are large and granules are not preferred due to their rough and bitter taste in the mouth. Since a new formulation of smaller tablets (sTab, 1 cTab = 1-gram granules = 4 sTab) was approved, a study regarding the usability of sTab in pediatric patients was conducted. Children who started taking sTab of the ST combination at our hospital between August 2021 and August 2022 were included. Using an anonymous questionnaire, the dosage of ST combinations, the child's response (3-point visual scale: positive, neutral, or negative), preparation and administration time, and method of taking the drug were asked. Twenty-two patients (median age: 11.0 years) receiving cTab. Median (range) number of tablets per dose was 1 (0.5-1.5) tablet, and was 4 tablets (1.0-4.0) after switching to sTab. Twenty patients (median age: 5.0 years) receiving granules. Median (range) single dose was 0.75 (0.2-2.0) gram, and was 2.0 (1.0-4.0) tablets after switching to sTab. Post-dose reactions were positive in 5, neutral in 7, and negative in 10 cases for cTab, and positive in 1, neutral in 7, and negative in 12 cases for granules. After switching to sTab, 9, 13 and 0 cases, and 10, 9 and 1 cases were positive, neutral, and negative, respectively. Median preparation and administration times were decreased after switching to sTab in both cTab and granules groups. The frequency of dosage manipulations was also decreased. The switch to sTab improved acceptability, and decreased burden of administration, suggesting that sTab is a user-friendly formulation in pediatric medications.